2022
DOI: 10.48550/arxiv.2205.13303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaussian Universality of Linear Classifiers with Random Labels in High-Dimension

Abstract: While classical in many theoretical se ings, the assumption of Gaussian i.i.d. inputs is o en perceived as a strong limitation in the analysis of high-dimensional learning. In this study, we redeem this line of work in the case of generalized linear classi cation with random labels. Our main contribution is a rigorous proof that data coming from a range of generative models in high-dimensions have the same minimum training loss as Gaussian data with corresponding data covariance. In particular, our theorem cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous studies assessed the learning performance of cerebellum-like systems with a model Purkinje cell that associates random patterns of mossy fiber activity with one of two randomly assigned categories (Marr, 1969; Albus, 1971; Brunel et al, 2004; Babadi and Sompolinsky, 2014; Litwin-Kumar et al, 2017; Cayco-Gajic et al, 2017), a common benchmark for artificial learning systems (Gerace et al, 2022). In this case, a low coding level increases the dimension of the granule cell representation, permitting more associations to be stored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessed the learning performance of cerebellum-like systems with a model Purkinje cell that associates random patterns of mossy fiber activity with one of two randomly assigned categories (Marr, 1969; Albus, 1971; Brunel et al, 2004; Babadi and Sompolinsky, 2014; Litwin-Kumar et al, 2017; Cayco-Gajic et al, 2017), a common benchmark for artificial learning systems (Gerace et al, 2022). In this case, a low coding level increases the dimension of the granule cell representation, permitting more associations to be stored.…”
Section: Discussionmentioning
confidence: 99%
“…However, this setting is not as restrictive as it appears. In fact, recent studies have shown Gaussian universality for GLMs with a large class of features, wherein their asymptotic behaviors can be computed to leading order under a simpler model with Gaussian features [65,[75][76][77]. Utilizing this correspondence, the statistical physics-based method is expected to be a valuable tool for analyzing the statistical methods to find limitation in the conventional statistical theory, analyze the α ∼ O(1) region, and construct efficient algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…to be robust and hold for a larger class of random matrices. Rigorous proofs are presented in [65][66][67][68][69], where the asymptotic prediction is shown to have a universal limit (as p → ∞) with respect to random matrices with i.i.d. entries.…”
Section: Synthetic Data: Universality Of the Gaussian Designmentioning
confidence: 99%